O teorema fundamental da aritmética: jogos e problemas com alunos do sexto ano do ensino fundamental - Barbosa, Gabriela dos Santos (2008)
The present thesis has the purpose of carrying out an interventionist study for the introduction of the Fundamental Theorem of Arithmetic (FTA) and main concepts associated to it to students of the 6th Grade of Basic Education. In the research we intend to answer the following question: What are the arguments used by students in the significance process of the Fundamental Theorem of Arithmetic? For that purpose, we carried out a study with 22 students of a private school situated in the north zone of Rio de Janeiro. The group had already been in touch, according to the school s formal point of view, with the concepts related to the Fundamental Theorem of Arithmetic: multiples, divisors, prime and compound numbers and prime factors decomposition. The research has as theoretical fundamental, the Conceptual Fields Theory proposed by Vergnaud (1983, 2001) and the ideas of Campbell and Zazquis (2002) related to the learning process of concepts associated with the Basic Number Theory, which TFA belongs to. The method used a study divided into three stages. The first stage was the collective use of an initial evaluation. The second addressed the intervention stage, which was divided into three activity groups, and inserted into them, there were two intermediary evaluations. And, at last, the third corresponds to the use, also collective, of a final evaluation, with the same questions as the initial evaluation. Data was analysed from two perspectives, one directed to quantitative analysis, where we tried to relate the percentages of rights, with the help of the statistic package SPSS (Statistical Package for Social Sciences). The second perspective was data analysis from the qualitative point of view, aiming at identifying the type of mistakes made by students, as well as their strategies to solve problem-situations. The results showed that students had developed their own scheme to deal with concepts in construction. In this process, even if implicitly, a series of mathematic concepts present in students actions; is the teacher s function to create favourable conditions for the students to explain them